The FitSpirit approach for increasing physical activity in canadian teenage girls: protocol of a longitudinal, quasi-experimental study - Leduc, Geneviève; Gilbert, Jo-Anne; Ayotte, Alexandra; Moreau, Nicolas; Drapeau, Vicky; Lemoyne, Jean; Monthuy-Blanc, Johana; Tremblay, Jonathan; Mathieu, Marie-Eve (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Worldwide, most adolescent girls do not meet physical activity (PA) recommendations and very few PA programs are tailored specifically towards them. Even fewer information exists about the long-term effects of such programs. Some Canadian schools have implemented the FitSpirit PA intervention designed specifically for girls aged 12 to 17 years old. This paper describes the protocol of a quasi-experimental study evaluating long-term changes in health behaviours and outcomes following FitSpirit participation. Methods The study is conducted among schools that partner with FitSpirit every year. It started in 2018 and will be completed in 2022. The intervention comprises motivational talks, a turnkey running program, PA sessions and special events. Study participants fill out an online questionnaire twice a year. Follow-up questionnaires are sent at the end of each school year to the study participants who dropout from FitSpirit. The main outcome, changes in PA levels, is evaluated using questions validated for adolescents. Secondary outcomes are health (perceived health); lifestyle habits (sedentary activities, eating and sleeping habits); psychosocial outcomes (physical self-efficacy and body satisfaction); and FitSpirit appreciation (activity participation and satisfaction). Most questions originate from questionnaires validated for the adolescent population. Cross-sectional and longitudinal analyses will be performed. Discussion This study will provide one of the first longitudinal reports on the impact of a large extra-curricular PA intervention designed specifically for adolescent girls. The current study will uniquely contribute to PA research by assessing outcomes additional to PA levels, including markers of health, lifestyle habits and psychosocial determinants. Trial registration NCT, NCT03804151 , Registered on January 22, 2019; retrospectively registered.